Digital Politeness in Academic WhatsApp Communication: A Pragmatic Analysis of Student–Lecturer Interactions in Indonesian Higher Education - Arfandi, Viki Fahril; Naila, Faiqotun; Hidayanti, Sukria; Wahyuni, Titin; Khafi, Moh. Zainul; Hardiansyah, Framz (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to analyze digital politeness among university students in academic WhatsApp communication with lecturers at Universitas PGRI Sumenep. The research is grounded in the changing landscape of academic communication, where digital interaction increasingly replaces face-to-face exchanges, raising new challenges in maintaining politeness and professional etiquette. A descriptive survey design was employed with 20 purposively selected students as participants. Data were collected through a Google Form questionnaire consisting of five dimensions: linguistic politeness strategies, digital communication etiquette, perception of power and distance, cultural and contextual sensitivity, and self-reflection on digital behavior. The data were analyzed using descriptive statistics (mean, SD, frequency) and qualitative thematic analysis of open-ended responses. The results indicate that students exhibit a high level of digital politeness (M = 4.17, SD = 0.43). The highest dimension was cultural and contextual sensitivity (M = 4.48), showing that traditional values of respect and humility remain strong in digital communication. Students consistently used greetings, expressions of gratitude, and apology markers in their WhatsApp messages to lecturers. However, hierarchical awareness appeared more flexible, reflecting a shift from formality-based to relationship-based politeness. These findings extend Brown and Levinson’s (1987) politeness theory into the domain of digital pragmatics, emphasizing that technology does not diminish politeness but reshapes it to fit new communicative contexts. The study recommends that universities incorporate digital communication ethics training into academic literacy programs to foster respectful and effective online interaction.